Governance of state zakat institution and its impact on zakat payment compliance : the case of the general authority of zakat and tax, Saudi Arabia - Sawmar, Abdulsalam Ahmed (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
Zakat institutions have a crucial role within the Islamic financial system, which is to maintain the prosperity and social harmony in Muslim communities. However, the role of current zakat institutions has been insufficient, which can be attributed to two main factors, i.e. inefficient zakat management and low zakat payment compliance. Hence, this study attempted to investigate these two factors in the Saudi Arabia case which has a regulated zakat system that could produce significant impacts from zakat contributions, whether locally or even abroad. Accordingly, the study adopted a mixed-method approach to investigate zakat compliance issues and examine the influence of governance-related factors of the Saudi Zakat Authority, the GAZT, on zakat payment compliance. Based on an extensive review of the literature and the analysis of qualitative data collected via interviews with zakat experts in SA, the study has developed the Zakat Governance-Compliance Relationship (ZGCR) model. In addition, the analysis of the qualitative data suggested several issues affecting zakat payers' compliance in the GAZT context. These issues included the lack of control mechanisms that ensure zakat payers' compliance, the perceived image of the GAZT role in relation to zakat, the lack of trust, and issues affecting the perceived procedural fairness. Subsequently, the quantitative process involved testing the developed ZGCR model using questionnaire survey on actual zakat payers in SA. Accordingly, the findings based on the analysis of 125 questionnaires using PLS-SEM technique suggested that the perceived transparency and disclosure and the perceived procedural fairness had significant positive relationships with zakat payment compliance. In addition, trust was found to have a mediating effect on the relationship between the perceived governance of the GAZT and zakat payment compliance. However, two governance-related factors showed insignificant relationships with zakat compliance, which are the perceived administration and the perceived performance of the GAZT. Overall, the findings of this study have contributed to zakat literature and provided practical implications to zakat administrators, especially the GAZT. Limitations of the study and suggestions for future research were highlighted in the Final Chapter. Keywords: Governance, state zakat institutions, zakat compliance, trust, Saudi Arabia